Kampanye Politik Kampanye Politik Pilkada Pasangan Calon Wali Kota Tangerang Selatan Siti Nur Azizah-Ruhamaben - Mujab, Saeful (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2022)
The purpose of this research was specifically to determine the political campaign of the candidate pair for Mayor Election of South Tangerang (Tangsel), Siti Nur Azizah-Ruhamaben during the Covid-19 pandemic. The 2020 Mayor Election was like a war between dynasties, because of the candidates have a political power based on their families. The candidate of H. Muhamad and Rahayu Saraswati Djojohadikusumo have a connection with the Minister of Defense, Prabowo Subianto which was her uncle . While the other candidates, Siti Nur Azizah was the daughter of Vice President Ma'ruf Amin. Meanwhile the another one, Pilar Saga Ichsan, was the son of the Regent of Serang, Ratu Tatu which was the younger sister of the former Banten Governor, Ratu Atut Chosiyah. The author used a qualitative research method with a descriptive approach. The results of this research were the political campaign of Siti Nur Azizah-Ruhamaben in the 2020 Mayor Election still focuses on offline campaigns. Procurement of props or outdoor media and greeting residents directly (including blusukan). Azizah-Ruhamaben also intensifies campaigns virtually or digitally, such as through social media or other digital applications such as WhatsAap groups and also creates and intensively campaigns on webs and Blogspot, and conducts character friendships through zoom meetings. In addition, Azizah–Ruhamaben integrated the two campaigns, one of which was by carrying out a drive-in declaration. The drive-in declaration has become a new innovation related to campaigns during the pandemic. Keywords: Campaign, Pilkada, Politic